A Microcomputer-based GNSS Scintillation Monitor using Low-Cost Receiver - Orongan Manuel Allan; Deleña Miemarc John; Macalalad Ernest; Marloun Sejera; Hsiao Tung Yuan (E3S Web of Conferences)
We improve upon previous low-cost radio scintillation monitor designs by implementing onboard processing and display capabilities to produce a more comprehensive device. The proposed design uses a U-blox EVK-6T’s GPS receiver, providing data updates at a rate of 1Hz, and a Raspberry Pi 4. The RPi calculates the S4c index with both a three-minute and a five-minute duration, then saves all the raw data and S4c values onto a locally stored CSV file. The proposed design has been successfully implemented, having been able to log all raw and calculated data and display the three-minute and five-minute S4c values on a plot with a temporal range from 00 UT to 24 UT. In addition to these features, we successfully validate the accuracy of our low-cost radio scintillation monitor by finding a high correlation between its C/No output to that of a high-rate receiver when performing simultaneous measurements from the same receiving antenna. The S4c values calculated from these C/No measurements also proved to be accurate as they demonstrated moderate correlation on non-scintillated days and high correlation on scintillated days.